Designing Reflection and Symmetry Learning by Using Math Traditional Dance in Primary School - Yullys Helsa; Yusuf Hartono (Journal on Mathematics Education, 2011)
The innovation of education is an important point of Pendidikan Matematika Realistik Indonesia (PMRI), one of them through traditional dance as a context of national cultural. Dance that collaborated with concept of mathematics, it is called Math Traditional Dance. This research aims to produce learning line (specific) the material of reflection and symmetry. The research method used is design research that consisted of preparing for the experiments, teaching experiments, and retrospective analysis. Data collected through observation, interviews, documentation and field notes. This research was conducted with 22 students in MIN 2 Palembang. From the try out that is obtained from the formal to the informal learning described in the learning process, so that support learning process of mirroring and symmetry for the students in grade four in elementary school.